Calling non-governmental organisations to strengthen primary health care: Lessons following Alma-Ata - Megan Landes; Colin Pfaff; Meseret Zerihun; Dawit Wondimagegn; Sumeet Sodhi; Katherine Rouleau; Michael R. Kidd (AOSIS, 2019)
Background: The Alma-Ata Declaration's commitment to primary health care (PHC) reaches its 40th anniversary in 2018. Over the last 40 years, the number of non-governmental organisations (NGOs) working in low-income countries (LICs) has rapidly multiplied, and over time, NGOs have both positively and negatively impacted equity, effectiveness, appropriateness and efficiency of PHC systems in LICs. Aim: The authors aim to demonstrate that at the 40th anniversary of the Alma-Ata Declaration's commitment to PHC, NGOs are particularly poised to strengthen PHC in LICs. Methods: In this letter, the authors reflect on how NGOs have both positively and negatively impacted equity, effectiveness, appropriateness and efficiency of PHC systems based on their experience working with NGOs in LICs. Results: NGOs are poised to strengthen PHC in LICs in four distinct ways: assisting with local human resources development, strengthening local information systems, enabling community-based health services and testing innovative service delivery projects. Conclusions: The authors call for NGOs to commit their expertise and resources to long-term strengthening of PHC in LICs and to critically examine the factors that prevent or assist them in this goal. As the principles of Alma-Ata are renewed, NGOs should be responsibly engaged in strengthening the declaration's goal of 'health for all'.